Superior Hydrazine Electrooxidation Activities on Tin and Zirconium Promoted ZSM-5 Zeolite Catalyst - Yildiz, Derya; Kaya, Sefika; Ozok-Arici, Omruye; Çağlar, Aykut; Kivrak, Arif; Kivrak, Hilal; Çağlar, Aykut (Wiley, 2025)
Direct fuel cells, such as direct hydrazine fuel cells (DHFC), are considered environmentally friendly alternative energy technologies with great potential for the future. Hydrazine, used as a liquid fuel, is particularly advantageous due to its high cell voltage and energy density. In this study, the electrocatalytic potential of SnZr/ZSM-5 catalysts synthesized with wet impregnation at various molar ratios is investigated for hydrazine oxidation. The catalyst is characterized by XPS, ICP-MS, XRD, FTIR, SEM-EDX, and TEM techniques. Additionally, thermal characterization of this catalyst is performed with temperature-programmed reduction (TPR), temperature-programmed oxidation (TPO), and temperature-programmed desorption (TPD). The catalytic activities of ZSM-5-supported monometallic and bimetallic catalysts are determined using electrochemical measurements such as cyclic voltammetry (CV), chronoamperometry (CA), and electrochemical impedance spectroscopy (EIS) for direct hydrazine fuel cell (DHFC). The highest catalytic activity achieved is 44.874 mA cm-2 for SnZr(50:50)/ZSM-5 catalyst, revealing that Zr addition to Sn improves the electrocatalytic activity of bimetallic catalysts compared to monometallic catalysts. The long-term current density and stability of SnZr(50:50)/ZSM-5 catalyst are taken at 0.6 V. EIS measurements indicated that the lowest charge transfer resistance is at 0.6 V, consistent with CV and CA measurements. SnZr(50:50)/ZSM-5 provides a new perspective as an anode catalyst for DHFC applications.
Keywords: Electrocatalyst; Fuel-Cell; Hydrazine Electrooxidation; Sn; Zr; Zsm-5